METHODOLOGICAL APPROACHES TO DETERMINING THE HISTORICAL AND CULTURAL IDENTITY OF THE PEOPLES OF DAGESTAN: RUSSIAN-ENGLISH DISCOURSE (Review on Robert Chenciner, Magomedkhan Magomedkhanov. Dagestan, history, ethnography, identity. Milton Keynes, UK: Routledge, Taylor & Francis Group, 2021. – 263 pages, 7 maps, 26 images) - Sadovoj, Aleksandr Nikolaevic (History, Archeology and Ethnography of the Caucasus, 2025)
This review critically examines the 2021 English-language publication “Dagestan, history, ethnography, identity” by Doctor of Historical Sciences M.M. Magomedkhanov (Russia) and Robert Chenciner (Great Britain). Notably, this monograph represents a pioneering effort within Russian historiography to systematically analyze the long-term social trends shaping contemporary Dagestani identity, tracing their influence from the Middle Ages to the present. The authors’ discourse employs the methodological framework of the systems approach, a perspective with established roots in Russian historical scholarship since the latter half of the 20th century.
Keywords: peoples of Dagestan; identity; traditional culture; Russian-English discourse; research methodology